Pembelajaran Pendidikan Agama Islam di Pendidikan Anak Usia Dini (PAUD) - Titin Faiqoh; Muh. Rodhi Zamzami; Naila Nahdiyah (AJMIE: Alhikam Journal of Multidisciplinary Islamic Education, 2024)
This research aims to analyze how to plan, implement and evaluate Islamic Religious Education learning in Early Childhood Education (PAUD). This research uses a qualitative approach with a case study type. Data analysis uses content analysis. The results of this research are Islamic Religious Education learning planning in PAUD which is carried out in 2 forms, namely the weekly learning implementation plan (RPPM) and the daily learning implementation plan (RPPH).  Implementation of Islamic Religious Education learning in early childhood must pay attention to the organization of the learning environment, models and methods of Islamic Religious Education learning. Evaluation of Islamic Religious Education learning in PAUD is carried out by observation, which can be done using technical anecdotal notes and checklists